2020
DOI: 10.1155/2020/2743058
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Propolis Inhibits the Proliferation of Human Gastric Cancer Cells by Inducing Apoptosis and Cell Cycle Arrest

Abstract: Special Chinese propolis sourced from the Changbai Mountains (CBMP) in Northeast China is rich in specific flavonoids and phenolic acids and its bioactivity has not been reported. This study aimed to investigate the antiproliferative effect of CBMP on cancer cells and its molecular mechanisms. Different cancer cell lines were treated with the ethanol extracts of CBMP for 24 hours before the cell viability and mechanism measurements. The results showed CBMP had weak activities against human pancreatic cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Some of the published research papers only state the effect of propolis and its components on the inhibition of the proliferation process without penetrating the molecular mechanism [ 9 , 16 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Nevertheless, there are also research results that bring these mechanisms closer.…”
Section: Mechanisms Of Anticancer Activity Of Propolis and Its Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the published research papers only state the effect of propolis and its components on the inhibition of the proliferation process without penetrating the molecular mechanism [ 9 , 16 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Nevertheless, there are also research results that bring these mechanisms closer.…”
Section: Mechanisms Of Anticancer Activity Of Propolis and Its Compoundsmentioning
confidence: 99%
“…The release of cytochrome C from mitochondria to the cytoplasm is observed, as well as the activation of cleaved caspases (8, 9, and 3) and PARP. Meanwhile, pro-apoptotic protein TP53 is also activated after CBMP treatment [ 65 ].…”
Section: Mechanisms Of Anticancer Activity Of Propolis and Its Compoundsmentioning
confidence: 99%
“…As balanced interactions between cyclins, cyclin-dependent kinases (CDK), and CDK inhibitors (CDI) regulate progression through the cell cycle [ 132 ], altered expression of the cell-cycle-specific proteins by dietary components potentially may sustain the proliferation of neoplastic cells and serve as “effect” biomarkers of their cytotoxic activity. The phenolic compounds of propolis, such as genistein, quercetin, kaempferol, myricetin, luteolin, chrysin, and apigenin, have been confirmed to modulate cell proliferation through an effect on the cell cycle by inducing CDI (p21 and p27) and inhibiting CDK4, CDK2, cyclin D1, and cyclin E [ 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. Kabała-Dzik et al [ 49 ] compared caffeic acid (CA) and CAPE activity on triple-negative human Caucasian breast adenocarcinoma cell line (MDA-MB-231).…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…Algerian propolis and its combination with doxorubicin decreased cell viability, prevented cell proliferation and cell cycle progression, induced apoptosis by activating caspase-3 and -9 activities, and increased the accumulation of chemotherapeutic drugs in MDA-MB-231 cells by blocking P-gp function and cell cycle arrest in the S phase [ 136 ]. Jiang and co-authors also demonstrated that Chinese propolis selectively inhibits the proliferation of human gastric cancer SGC-7901 cells by triggering both death receptor- and mitochondria-induced apoptosis, and cell cycle arrest in the S phase [ 137 ]. In the study by Zang et al [ 138 ], it was shown that flavones (luteolin, chrysin, and apigenin) and flavonols (quercetin, kaempferol, and myricetin) can induce cytotoxicity to OE33 cells (a human esophageal adenocarcinoma cell line) by causing G 2 /M arrest and induction of apoptosis.…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…Other authors have also observed this effect. Jiang et al [ 37 ] reported that Special Chinese propolis sourced from the Changbai Mountains showed anti-proliferation activity in SGC-7901 human gastric cancer cells by inducing both death receptor-induced apoptosis and mitochondria-mediated apoptosis, as well as cell cycle arrest in the S-phase. In this study, it has been observed that both PPE and MPE induced apoptosis in each glioma cell line (DASC, LN-18, T98G) ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%